Comparing mouse and human brains - Hovy Ho-Wai Wong; Christina You Chien Chou; Alanna Jean Watt; Per Jesper Sjöström (eLife, 2023)
Inhibitory circuit motifs in the mouse brain and the human brain are strikingly similar.